Faktor risiko dan gejala osteoporosis pada komunitas dewasa di Desa Ibul Besar Pemulutan Ogan Ilir Sumatera Selatan - Umi Partan, Radiyati; Reagan, Muhammad; Hermansyah, Hermansyah; Darma, Surya; Muthia, Putri; Mediarty, Mediarty; Indrajaya, Taufik; Kurniati, Nova; Riviati, Nur; Yuniza, Yuniza (Fakultas Kedokteran Universitas Sriwijaya, 2021)
. Osteoporosis is a worldwide health issue. The microarchitecture of the bone is deteriorating, which increases the risk of fracture and disability. As the Indonesian people's life expectancy increases, the incidence of osteoporosis rises, making it more difficult to manage. This community service is carried out as a form of preventive treatment in the adult community in the village of Ibul Besar III Pemulutan Ogan Ilir, South Sumatra, which is one of Sriwijaya University's guided villages, with counseling methods to increase knowledge and health checks for early detection of osteoporosis, as well as calcium supplementation. There were 81 participants in this activity, with numerous dominant risk factors for osteoporosis identified, including female gender, menopausal state, and age above 50. Musculoskeletal symptoms, such as pain in the waist and back, which can be a consequence of osteoporosis, are more common than non-musculoskeletal symptoms.